Nonfatal agriculture injuries in children - A retrospective study - Huda, Farhanul; Wasim, Sanober (Indian Journal of Child Health, 2016)
Introduction: A larger proportion of the population in the world is involved in agriculture. Agricultural injuries are a major cause of morbidity and mortality both in developed as well as developing countries. These injuries can occur in all age groups. Objective: Since India is a predominantly agricultural country, we undertook this study to find out the pattern of agricultural injuries in children. Materials and Methods: This is a retrospective hospital-based study. Children <18 years of age, who presented to the hospital with agriculture-related injury from January 2009 to January 2013, were included in the study. The following data were recovered for each case - age, sex, type and cause of injury, and the body part involved. All fatalities were excluded from the study. Simple frequencies and percentages were obtained for various variables. Results: A total of 146 patients were included in the study. 94 (64.4%) were males and 52 (35.6%) were females. The most common age group involved was 7-13 years. Fractures and dislocation were the most common injuries (29.7%). Most of the injuries were to the upper extremities (57.3%). There was a wide variety of causes of agricultural injury in our study, falls and slips being the most common cause. Conclusion: Our study shows that males in the age group of 7-13 years were the most frequent victims of agricultural injuries. Falls and slips were the most common mechanism of injury with fracture and dislocations being the most common type of injury. The results from this study will help in identifying the risk factors for agriculture injuries in children and also to look for the prevention measures to be applied.